Analisis Implementasi Strategi Contextual Teaching and Learning pada Pembelajaran Fiqih di Kelas XI IPS 1 Madrasah Aliyah Swasta Darul Hadits Huta Baringin - Harahap, Hasnah Azhari; Zulhimmah , Zulhimmah; Efendi , Manahan; Nurhayani , Nurhayani (CV. Lenggogeni Data Publishing, 2024)
The essence of education as stated in the preamble to the 1945 Constitution is to make the life of the nation intelligent. This means creating citizens who have creative and innovative abilities in applying knowledge to overcome various challenges in social, national and state life. The aim of this research is to find out how innovations are carried out by teachers at the Darul Hadits Huta Baringin Private Madrasah Aliyah, especially in fiqh subjects with riba' teaching material. The method used in this research is a qualitative method, namely field research, which was directly carried out at MAS Darul Hadits Hutabaringin by collecting data through interviews with several sources, including teachers of class XI IPS 1 students who were the target of implementing this strategy. The implementation of the strategy at MAS Darul Hadits Hutabaringin is the Contextual Teaching and Learning (CTL) strategy, by referring to the concepts, researchers see that the implementation of CTL has been successfully carried out at MAS Darul Hadits Huta Baringin with good results. So, to further improve the quality of education there, learning strategies and evaluation must continue to be carried out.